اتجاهات أعضاء هيئة التدريس بجامعة الإمام المهدي كليتي التربية التمريض نحو استخدام التقنيات الحديثة في التدريس. - د. حسن الفاتح الحسين محمد المبارك (White Nile Journal for Studies and Research, 2019)
The purpose of this study is to identify the trends of the faculty members al AL-Imam Al-Mahdi University, the colleges of education and nursing in using the modem means of teaching, by zlarifying the reality of the application of modem methods, and the extent of their tamiliarity with the faculty members and the types of obstacles facing them. The study problem is emphasized in this question (What are the directions of the members of the Faculty of Education, Nursing in AL-Imam Al-Mahdi University in using the modem methods in teaching? The researcher sad the descriptive analytical method, because it is best suited for conducting this study and the most effective in achieving its objectives. The sample of the study consisted of (50) male professors and female professors in the faculties of education and nursing at AL-Imam Al-Mahdi University. The study tool represented in the questionnaire which was designed and arbitrated by a number of specialists in the feit of education and then the use of statistical packages for social sciences (SPSS) to analyze the results of the study. The study found the following results: The realty of the use of modem means by members of the faculty at the University of Imam Mahdi in the facultes of education and nursing through the variety of their types, and improves the performance of the faculty member. The modern means reduces the effort and time in teaching and types of amart boant, models, multimedia, and data and video projector. While the obstacles facing the use of modem means is the lack of sufficient material support for use and the difficulty of implementation, and weak training of the faculty to use based on the results of the study. The study recommends the need